Production Process Evaluation of a Job Shop Fabrication Line – A Case Study at a Door Manufacturer - Elia Oey; Albert Brilliant Limita; Harold Adhitjan (Institute of Research and Community Outreach - Petra Christian University, 2018)
With the increasing market competitiveness, it is crucial for company to remain effective and efficient in its Operation Management. Production process is one of major areas where company seeks to improve its production capability in order to remain competitive. The research was a case study in a door fabrication line. The production process is a job shop process type which consists of several inter-linked and inter-dependent sub-processes with shared resources. The study used simulation methodology and Simio software to better understand and analyze the complexity of the process. The study fed few controlled and uncontrolled input variables into the simulation models and analyzed on how to improve some output/response variables. Six scenarios were analyzed during experimentation leading to the best scenario 7 giving improvement in term of crew utilization, average time, and number of entity in the system. Besides giving recommendations to the studied company, the study also successfully demonstrated on how simulation can be used to mimic different kinds of process logic in a job shop production process.